Perencanaan Pendidikan Metode Nilai Tambah Tahfid Al-Qur’an Dan Implementasi Pada SD Muhammad Al-Unaizy - Irwan Desiharto; Siti Qomariyah; Dede Maulana Malik (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The reality that occurs today, religious education has received less attention and is often criticized by the community because there are a number of students and graduates who are unable to read the Quran properly and correctly. One of the efforts to overcome this problem is to hold a Qur'an tahfidz program. Such is the close relationship between education and the Qur'an, it is impossible to reach the point when talking about education without the Qur'an This study aims to find out how the planning of the Qur'anic tahfidz value-added method and its implementation in SD Muhammad Al-Unaizy and This researcher used qualitative research methods of description of learning tahfidz al-Qur'an. Based on the findings encountered by researchers in the field, it can then be concluded that SD Muhammad Al-Unaizy has a Quran tahfidz program planning and implementing the Qur'an tahfidz value-added program thoroughly according to the previously planned program.